Pengaruh Kualitas Pelayanan Dan Harga Terhadap Kepuasan Konsumen Pada Layanan Transportasi Online Gojek Di Jakarta Utara: The Effect of Service Quality and Price on Customer Satisfaction with Gojek Online Transportation Services in North Jakarta - Hakiki Panreist Meillid; Sofyan Marwansyah (CV Warnak Johanna Nusantara, 2025)
Technological advancements have triggered major transformations in various sectors, including the transportation industry. Application-based online transportation services service such as Gojek, particularly the GoRide service, have now become one of the preffered solutions for the public. This study aims to explore the influence of service quality and price on consumer satisfaction with Gojek in North Jakarta. The population in this study includes 100 respondents who are users of the GoRide (Gojek) online transportation service in North Jakarta. A simple random sampling technique was used for sampling. Data were collected throught a questionnaire measured using a likert scale. The data were analyzed using data quality tests, classical assumption tests, hypothesis testing, the coefficient of determination test, and regression coefficient test utilizing SPSS version 26 software. The results of the study indicate that service quality has a significant partial influence on consumer satisfaction. Price also has a significant influence on consumer statisfaction. Simultaneously, service quality and price have a significant influence on consumer satisfaction.